2005
DOI: 10.1002/zaac.200500356
|View full text |Cite
|
Sign up to set email alerts
|

Differing Coordination Modes of (O‐Alkyl)‐p‐Ethoxyphenyldithiophosphonato Ligands in Copper(I), Silver(I) and Gold(I) Triphenylphosphine Complexes

Abstract: The three (O‐methyl)‐p‐ethoxyphenyldithiophosphonato triphenylphosphine complexes of copper, silver and gold, [(Ph3P)nM{S2P(OMe)C6H4OEt‐p}] (M = Cu, n = 2; M = Ag, Au, n = 1) investigated structurally by X‐ray diffraction exhibit remarkable structural differences. The copper compound is a four‐coordinate chelate monomer with Cu–S 2.4417(6) and 2.5048(6) Å; P–Cu–S 104.24(2)–114.01(2)°; Cu–S–P 82.49(3)° and 80.85(2)°. The silver compound is a cyclic dimer with bridging dithiophosphonato ligands and three‐coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Data collection: APEX2 (Bruker, 2007); cell refinement: SAINT (Bruker, 2007); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: ORTEP-3 for Windows (Farrugia, 1997); software used to prepare material for publication: WinGX (Farrugia, 1999) and PLATON (Spek, 2009). Dithiophosphorus compounds and their complexes have been widely investigated in last decades (Heiduc et al, 2006;Karakuş et al, 2007;Gataulina et al, 2008). They have been utilized in agricultural, industrial and medicinal products such as additive to lubricant oils, solvent extraction reagents for metals, floatation agents for minerals, pectidites and insecticides (Thomas et al, 2001;Gray et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collection: APEX2 (Bruker, 2007); cell refinement: SAINT (Bruker, 2007); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: ORTEP-3 for Windows (Farrugia, 1997); software used to prepare material for publication: WinGX (Farrugia, 1999) and PLATON (Spek, 2009). Dithiophosphorus compounds and their complexes have been widely investigated in last decades (Heiduc et al, 2006;Karakuş et al, 2007;Gataulina et al, 2008). They have been utilized in agricultural, industrial and medicinal products such as additive to lubricant oils, solvent extraction reagents for metals, floatation agents for minerals, pectidites and insecticides (Thomas et al, 2001;Gray et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…For dithiophosphorus compounds and their complexes, see: Heiduc et al (2006); Karakuş et al (2007); Gataulina et al (2008). For the roles of dithiophosphorus compounds in agricultural, industrial and medicinal products such as additives to lubricant oils, solvent extraction reagents for metals, floatation agents for minerals, pesticides and insecticides, see: Thomas et al (2001); Gray et al (2003).…”
Section: Related Literaturementioning
confidence: 99%
“…Current synthetic efforts in the field concentrate on metal complexes with ligands designed by formally replacing O atoms in phosphate ions with OR, SR, S, Se, OSe and combinations thereof, and ultimately on the construction of larger molecular aggregates. [15][16][17][18][19][20] In previous work, it was shown that reactions of metal salts MX (X = alkoxide, thiolate, carboxylate) with Lawessons reagent (L.R.) [{RP(S)A C H T U N G T R E N N U N G (m-S)} 2 ] (R = 4-anisyl) [21] or the analogous Se compound Woollins reagent (W.R.) [{PhP(Se)A C H T U N G T R E N N U N G (m-Se)} 2 ] [8,22] offer an alternative route to complexes containing P/S-or P/Se-based anionic ligands.…”
Section: Pe [Rp(e)a C H T U N G T R E N N U N G (Esime 3 ) 2 ] [{Rpmentioning
confidence: 97%
“…The IR spectrum of the ligands and their complexes showed two characteristic bands at around 692–642 cm −1 and 582 – 515 cm −1 which are assigned to ν as (PS 2 ) and ν s (PS 2 ), respectively [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%